PENGARUH LITERASI KEUANGAN MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS RIAU TERHADAP KEMAMPUAN PENGELOLAAN KEUANGAN - Titik Sunarmi; Gimin Gimin; RM. Riadi RM. Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Based on the observations, the financial management of S1 Economics Education students from the University of Riau class 2017-2019 is mostly oriented towards consumption and benefits in the present. In fact, in the learning process students learn concepts or knowledge about finance. Thus, students have not used the knowledge they have to bring up financial attitudes and behaviors. Therefore, the purpose of this research is to determine the effect of financial literacy of economic education student in Riau University on financial management ability. The approach in this research is a quantitative approach with a population of 228 students and a sample of 146 students. Sampling using the Slovin formula and proportionate stratified random sampling technique. Methods of data collection using a questionnaire, with a semantic differential scale. The data analysis technique used is simple linear regression analysis with the help of SPSS. The results showed that significantly the financial literacy of economic education student in Riau University had a positive effect on financial management ability.Key Words: Financial Literacy, College Student’s Financial Management